RATIONAL DIAGNOSTIC METHODS AND ALGORITHMS FOR DETECTING KIDNEY DISEASES IN CHILDREN (ENGLISH) - A.E. Naushabaeva; K.A. Kabulbaev; A.L. Rumyantsev; V. Brocker; J. Ehrich (Union of pediatricians of Russia, 2009)
This review summarises the basic and essential laboratory tools for identifying and differentiating renal diseases in children. Furthermore, it describes the limits of out-dated techniques and the potential of new diagnostic laboratory methods. Diagnostic algorithms are shown which, together with supplementary methods allow, firstly, the diagnosis of the location of renal damage levels; secondly, clarification of the etiology of the disease and, thirdly, the characterisation of the stage of the renal function disorder.Key words: kidney diseases, diagnostics, symptoms of renal damage, children.